2005
DOI: 10.1158/0008-5472.can-05-2474
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Oncoprotein Blocks Glycogen Synthase Kinase 3β–Mediated Phosphorylation and Degradation of β-Catenin

Abstract: Dysregulation of B-catenin is of importance to the development of diverse human malignancies. The MUC1 oncoprotein is aberrantly overexpressed by most human carcinomas and associates with B-catenin. However, the functional significance of the MUC1-B-catenin interaction is not known. Here, we show that MUC1 increases B-catenin levels in the cytoplasm and nucleus of carcinoma cells. Previous studies have shown that glycogen synthase kinase 3B (GSK3B) phosphorylates B-catenin and thereby targets it for proteosoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
306
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 212 publications
(325 citation statements)
references
References 48 publications
(77 reference statements)
16
306
1
2
Order By: Relevance
“…Estimates indicate that ~800,000 of the 1.4 million tumors diagnosed annually in the US overexpress MUC1. Recent studies have demonstrated that the overexpression of MUC1 induces transformation (6) and that the oncogenic sequences reside in the MUC1 C-terminal subunit (20,44). However, no information is available regarding the origin of the MUC1-C extracellular and cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Estimates indicate that ~800,000 of the 1.4 million tumors diagnosed annually in the US overexpress MUC1. Recent studies have demonstrated that the overexpression of MUC1 induces transformation (6) and that the oncogenic sequences reside in the MUC1 C-terminal subunit (20,44). However, no information is available regarding the origin of the MUC1-C extracellular and cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
“…The MUC1-CD binds to ß-catenin and increases ß-catenin levels by blocking its degradation (20). Moreover, MUC1-CD is sufficient to induce transformation by a mechanism that is at least in part dependent on the interaction with ß-catenin (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations